On algebraic graph theory and non-bijectivemultivariate maps in cryptography - Ustimenko, V. (Algebra and Discrete Mathematics, 2015)
Special family of non-bijective multivariate maps Fn of Zmⁿ into itself is constructed for n = 2,3, ... and composite m.The map F is injective on Ωn = {x|x1+x2+: : : xn ∈ Zm*} and solution of the equation Fn(x) = b, x ∈ Ωn can be reduced to the solution of equation zr = α, z ∈ Zm*, (r, φ(m)) = 1. The “hidden RSA cryptosystem” is proposed. Similar construction is suggested for the case Ωn = Zm*ⁿ.